Bibliometric Analysis of Green Entrepreneurship Research in Higher Education: Trends and Future Research Directions - Prasetio, Bayu; Supardi, Endang; Kurniawati , Susanti; Mulyadi, Hari; Waspada, Ikaputera; Istikomah , Navik (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study analyzes trends, patterns, and future directions of green entrepreneurship in higher education using a bibliometric approach. By mapping scientific production, collaboration networks, and thematic evolution, it provides insights into its academic development and policy implications. Design/methodology/approach: This study employed bibliometric analysis using publications retrieved from the Scopus database. A keyword-based search strategy was used to identify relevant articles, which resulted in 48 final publications for analysis. Two analysis tools, VOSviewer and R Studio (Biblioshiny), were used to analyze co-citations, co-occurrence networks, author productivity evaluation, and keyword analysis. Research Findings: Research on green entrepreneurship in higher education is growing, with a focus on social sciences and business management. Developed countries lead in scientific production, while developing nations like Indonesia and Pakistan are emerging contributors. The field is shifting towards understanding how education fosters green entrepreneurial intentions. However, gaps remain in evaluating the real-world impact of green entrepreneurship programs. Theoretical Contribution/Originality: This study systematically maps the evolution of green entrepreneurship research, emphasizing its multidisciplinary nature and the need for better integration of environmental and technological aspects. It highlights curriculum development, learning models, and policy effectiveness as key future research areas while underscoring the potential for global collaboration in fostering sustainable entrepreneurship. Keywords: Green Entrepreneurship, Higher Education, Bibliometric, VOSviewer, R Studio